2021
DOI: 10.1002/ccd.29948
|View full text |Cite
|
Sign up to set email alerts
|

Surgical versus transcatheter aortic valve replacement in low‐risk patients: A long‐term propensity score‐matched analysis

Abstract: Background Recent studies suggest the use of transcatheter aortic valve implantation (TAVI) as an alternative to surgical aortic valve replacement (SAVR) in lower risk populations, but real‐world data are scarce. Methods Single‐center retrospective study of patients undergoing SAVR (between June 2009 and July 2016, n = 682 patients) or TAVI (between June 2009 and July 2017, n = 400 patients). Low surgical risk was defined as EuroSCORE II (ES II) < 4% for single noncoronary artery bypass graft procedure. TAVI p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…The copyright holder for this preprint this version posted March 24, 2023. ; https://doi.org/10.1101/2023.03.20.23287505 doi: medRxiv preprint survival analysis [11,[13][14][15][16][17][18][19][20][21][22]. One study was a randomized controlled trial and remaining ten studies were observational.…”
Section: Literature Selection Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted March 24, 2023. ; https://doi.org/10.1101/2023.03.20.23287505 doi: medRxiv preprint survival analysis [11,[13][14][15][16][17][18][19][20][21][22]. One study was a randomized controlled trial and remaining ten studies were observational.…”
Section: Literature Selection Resultsmentioning
confidence: 99%
“…A total of 11,987 studies were identified, published from 2002 to 2016, after removal of duplicates and evaluation based on the selection criteria, 12 studies were included in the meta-analysis (Figure 1). Eleven studies with a total of 5,458 patients were included in the survival analysis [11,[13][14][15][16][17][18][19][20][21][22]. One study was a randomized controlled trial and remaining ten studies were observational.…”
Section: Literature Selection Resultsmentioning
confidence: 99%
“…Eleven studies with a total of 5458 patients were included in the survival analysis. 11,[13][14][15][16][17][18][19][20][21][22] One study was a randomized controlled trial and remaining 10 studies were observational. Five studies with 1509 patients were included in the analysis of freedom from SVD.…”
Section: Literature Selection Resultsmentioning
confidence: 99%
“…A total of 11,987 studies were identified, published from 2002 to 2016, after removal of duplicates and evaluation based on the selection criteria, 12 studies were included in the meta‐analysis (Figure 1). Eleven studies with a total of 5458 patients were included in the survival analysis 11,13–22 . One study was a randomized controlled trial and remaining 10 studies were observational.…”
Section: Resultsmentioning
confidence: 99%